The mathematical modelling of the process of burden dissolving in superpower ark steel-making furnace - S. S. Brodski; O. I. Pavljuchenkov; V. Ju. Bolotov; E. V. Ivanov; A. D. Shevchenko; M. P. Gulajev; I. A. Pavljuchenkov; N. L. Mandel; D. K. Gribok (Литьë и металлургия)
There is developed and solved the mathematical model of dissolving process of burden in three-dimensional production, allowing for the peculiarities of modem technologies of steel melting in arc steel-making furnaces.